Peningkatan Hasil Belajar IPS Materi Perjuangan Para Tokoh Pejuang Pada Masa Penjajahan Belanda Dan Jepang Melalui Model Jigsaw - Rosfiani, Okta; Mardiyah, Mardiyah; Azaly, Intan; Lestari, Lisa Puji; Story, Siti Asmarwah Abd (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Based on the results of studying Social Sciences (IPS) class V SDI An Nuriyah Jagakarsa Concerning the Struggle of Warrior Figures During the Dutch and Japanese Colonial Period who still had not reached the specified KKM, namely 70. Of the 35 students, only 11 people (31.42%) were able to This is why research on improving social studies learning was carried out regarding improving social studies learning outcomes regarding the struggle of warrior figures during the Dutch and Japanese colonial period through jigsaw type cooperative learning. The aim of this assessment is to improve students' social studies learning outcomes regarding the struggle of warrior figures in during the Dutch and Japanese colonial period through jigsaw type cooperative learning. This research uses Classroom Action Research with a cycle system consisting of planning, implementation, observation and reflection. Based on the research results, it shows that students' learning completeness in each cycle has increased, this is shown in the pre-cycle students whose learning completeness was above KKM 70 was only 31.42%, in cycle 1 it increased to 62.86%, in cycle 2 it increased to 94.28%. Thus it can be concluded that the jigsaw type cooperative learning model can improve learning outcomes student.